Seroprevalence and Risk Factors of Chlamydia abortus Infection in Tibetan Sheep in Gansu Province, Northwest China - Si-Yuan Qin; Ming-Yang Yin; Wei Cong; Dong-Hui Zhou; Xiao-Xuan Zhang; Quan Zhao; Xing-Quan Zhu; Ji-Zhang Zhou; Ai-Dong Qian (The Scientific World Journal)
Chlamydia abortus, an important pathogen in a variety of animals, is associated with abortion in sheep. In the present study, 1732 blood samples, collected from Tibetan sheep between June 2013 and April 2014, were examined by the indirect hemagglutination (IHA) test, aiming to evaluate the seroprevalence and risk factors of C. abortus infection in Tibetan sheep. 323 of 1732 (18.65%) samples were seropositive for C. abortus antibodies at the cut-off of 1 : 16. A multivariate logistic regression analysis was used to evaluate the risk factors associated with seroprevalence, which could provide foundation to prevent and control C. abortus infection in Tibetan sheep. Gender of Tibetan sheep was left out of the final model because it is not significant in the logistic regression analysis (P>0.05). Region, season, and age were considered as major risk factors associated with C. abortus infection in Tibetan sheep. Our study revealed a widespread and high prevalence of C. abortus infection in Tibetan sheep in Gansu province, northwest China, with higher exposure risk in different seasons and ages and distinct geographical distribution.